AB-QTL analysis for â-glucan content in oats - Yu, Jianzhong; Beuch, Steffen; Herrmann, Matthias; Hackauf, Bernd (MTT, 2004)
The advanced-backcross QTL analysis (AB-QTL analysis), as proposed by Tanksley and Nelson (1996), was chosen as an directed approach to introduce QTLs for B-glucan content and other important traits from a genebank accession into cultivar breeding programmes. In this presentation first results from an oat AB-QTL project are presented. Three BC2S1 populations consisting of 98, 73 and 67 lines, respectively, were derived from the cross 'Iltis' x IA H611-447, the latter of which served as a donor for high â-glucan content. In 2003 the first field nursery was performed with the 237 BC2S4 families at three locations with two replications per location. The most important agronomical and quality traits have been analysed. Segregation between lines was evident in yield components and yield, plant height and quality parameters like â-glucan content. Some transgressive lines for yield and yield components were found and have to be validated in the next generations. The transgressive progenies did not outperform the most recent high-yielding cultivars. To find useful markers for the QTL analysis, 144 oat SSRs were screened, of which 26 were polymorphic between the parents and 5 showed segregation in the first population. Additionally, 128 EcoRI/MseI AFLP primer combinations were detected, of which 32 primer combinations showed 176 polymorphic bands between the parents. The polymorphic AFLP markers, together with STS markers, will be used to genotype the three populations, starting with the first population. This genotyping is on the way. Tanksley SD, Nelson JC 1996: Theoretical and Applied Genetics 92:191 203
Keywords: Ka; oats; Avena ssp.; B-Glucan; AB-QTL-analysis